Analysis of the Importance of Robotics Implementation to Increase Company Profits in Era 4.0 Using the Why-Why Analysis Method - Bari, Isyat Zain; Nizar, Aufa; Rayhan, Muhammad; Ramlan, Rosyadi; Novaliana, Mery; Prastyo, Yudi (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This research analyzes the positive impact of applying robotics in the manufacturing industry in the 4.0 era. The research results show that automation through robotics can significantly increase productivity, efficiency and product quality. In addition, robotics also contributes to reducing production costs and increasing the competitiveness of companies in the global market. This research aims to examine in depth the influence of the application of robotics technology on increasing the profitability of manufacturing companies in the industrial era 4.0. Through literature analysis and case studies, this research identifies several key factors that contribute to increasing profits, such as increasing production efficiency, reducing human errors, increasing production flexibility, and optimizing resource use. The results of this research provide important implications for manufacturing companies in making investment decisions in robotics technology to achieve competitive advantage. Era 4.0 is marked by rapid technological disruption, including the development of robotics. This research explores the crucial role of robotics in the transformation of the manufacturing industry. By leveraging data from companies that have adopted robotics, this research shows that investments in robotics not only improve productivity and product quality, but also enable companies to adapt quickly to changing market demands and dynamic industry trends.